Peran Latar Belakang Keluarga Terhadap Keberlangsungan Usaha dan Kesejahteraan Pengrajin Perak di Kabupaten Gianyar - Pratiwi, I Gusti Ayu Made Agung Mas Andriani; Kusmawan, I Made Hary (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2022)
The silver industry in Gianyar Regency is a business that has been carried out for generations, so it is not surprising that Gianyar Regency is known as a center for silver crafts. However, currently the condition of silver handicraft SMEs is in a stagnant condition and even tends to decline, especially with the Covid-19 pandemic so that it can have an impact on business continuity and the welfare of craftsmen. The purpose of this study was to examine the effect of family background on business continuity and the welfare of silver craftsmen in Gianyar Regency. The population in this study is 235 silver handicraft IKM. The research sample was determined using a purposive sampling method resulting in a total sample of 95 silver handicraft IKM. This study uses descriptive analysis techniques and quantitative analysis techniques with structural equation models or Structural Equation Modeling (SEM), especially Partial Least Square (PLS) with an analytical tool, namely SmartPLS. The results showed that (1) family background had a significant positive direct effect on the sustainability of the silver craftsmen's business in Gianyar Regency; (2) Family background and business continuity have a significant positive direct effect on the welfare of silver craftsmen in Gianyar Regency; and (3) business continuity mediating the influence of family background on the welfare of silver craftsmen in Gianyar Regency.